Implementation of Communication in the Education Process at SDIT X in Lamongan - Tri Marfiyanto (EDUTEC : Journal of Education And Technology, 2018)
Humans as social creatures will certainly not be able to escape communication, because communication is the need for everyone to be able to interact with others. So that one's life and quality depends on their ability to communicate. The purpose of this study is to describe the communication strategies used by teachers in the education process. This research is a field research. Here the authors collect data from the field by conducting direct investigations in the field to look for various problems that have relevance to research. From the results of the study the authors found that the communication strategy in the educational process used by the teacher did not refer to the theories of the experts but in their implementation partly matched the compatibility with expert theories. Communication strategies are prepared only for things that have been planned beforehand to be conveyed to students, while daily communication does not use strategies.